Peran Tenaga Kerja Wanita pada Industri Makanan Ledre Pisang di Kabupaten Bojonegoro - Richardus Widodo, Tiurma Wiliana Susanti Panjaitan Wardah (AGROKNOW, 2013)
Abstract. Small enterprises have good sustainability against economic changes occured in Indonesia recently. For the reason the development of small enterprises is very necessary since these enterprises still have many basic problems. The problems are including fund problem, specially working fund, marketing, distribution, raw material, and lack of human resources. Now days, 60% of about 30 million of small and medium entrepreneurs are female. One case is small enterprises of Ledre Pisang in Kabupaten of Bojonegoro. Most of them are carried out by housewives as an effort to support family income. As related to the female nature as entrepreneur, beside the responsibility for household issues, there are some more factors must be considered, such as pregnancy, give birth, and feed the children, where such roles can not be replaced by male. This researchâs purpose is to describe the role of female entrepreneur in sustainability and production of small ledre pisang industries.Â This research also investigates the effect of availability of raw material, price of raw material, fund, and product price to the sustainability of small ledre pisang industries in Kabupaten of Bojonegoro. The result of the research shows the role of female entrepreneur is very important in ledre pisang industries because of their skill can not be substituted by other family members. The income of female entrepreneur from these industries can support their family daily need. During carrying out the business, it is shown that female nature such as pregnancy period, gives birth, and feed the children, affects the sustainability of ledre pisang production. Among all the respondent, 79% of them say production time reduced during that condition and 8% of them say they do not produce at all temporary. Statistic analysis of factors affecting the sustainability of industry shows that availability of raw material, price of raw material, and product price do not show significant affect to the sustainability of the industries.Kata kunci: tenaga kerja wanita, usaha kecil menengah